Toward High‐Performance Diamond Electronics: Control and Annihilation of Dislocation Propagation by Metal‐Assisted Termination. Issue 21 (18th September 2019) - Ohmagari, Shinya; Yamada, Hideaki; Tsubouchi, Nobuteru; Umezawa, Hitoshi; Chayahara, Akiyoshi; Mokuno, Yoshiaki; Takeuchi, Daisuke
Abstract : A major obstacle limiting diamond electronics is dislocations, which deteriorate device properties. As threading dislocations (TDs) are normally inherited from the substrate to the epitaxial layer, control and annihilation of their propagation are important. Herein, metal‐assisted termination (MAT), in which the propagation of dislocations is suppressed by in situ metal doping, is proposed. Heavy W doping is realized by a hot‐filament (HF) chemical vapor deposition (CVD) using heated wires at a high temperature of >2400‐K. A large reduction of TD density is confirmed by cathodoluminescence studies and etch‐pit analysis. The impact of dislocation reduction is investigated electrically. After insertion of the MAT buffer layer, Schottky barrier diodes (SBDs) show improved rectifying action and highly uniform characteristics even when substrates with high dislocation densities (mosaic and heteroepitaxial wafers) are used. The 3D structure of dislocation propagation is successfully captured by two‐photon‐excited photoluminescence (2PPL) imaging of Band‐A luminescence. The 2PPL Band‐A luminescence (without band‐edge excitation) shows high spatial resolution in the depth direction. An abrupt decrease in TD density is captured for heteroepitaxial substrates with an inserted MAT buffer layer. The MAT technique provides an effective approach to realize high‐performance diamond electronics. Abstract : A major obstacle limiting diamond electronics is dislocations, which deteriorate device properties. Herein, metal‐assisted termination (MAT), in which a propagation of dislocation is suppressed by metal impurities or its local strains, is proposed. MAT is accomplished by hot‐filament chemical vapor deposition using heated W wires at a high temperature >2400 K. Reduction of dislocation density and improved electrical characteristics are presented.